Green energy from working surfaces: a contact electrification–enabled data theft protection and monitoring smart table. (December 2020) - Chandrasekhar, A.; Vivekananthan, V.; Khandelwal, G.; Kim, W.J.; Kim, S.-J.
Abstract: Data theft from the desktop system using devices capable of storing data is a serious problem that causes great harm to an individual or a company. It is essential to excogitate a way to reduce the problem. The triboelectric nanogenerator (TENG), recently introduced as a light-weight, easy-to-design energy harvester, works on the coupling of electromagnetic induction and contact electrification. In this work, a TENG is used to incorporate a smart feature in the table which triggers an alarm if an intruder is using the desk. The TENG works in the single-electrode contact-separation mode and in the sliding mode. The Kapton backed by aluminum is used as active triboelectric layers while the material on apparels or hand skin acts as opposite triboelectric material. The device is systematically studied for its electrical performance using materials such as jeans, cotton, paper, etc. The device gives the highest output voltage and current of ~200 V and 2.2 μA in case of paper. Finally, a smart table is demonstrated using the as-fabricated TENG coupled with the Arduino board which triggers an alarm if a person is accessing the desk. This work can extend the application of the TENG for the development of smart furnitures. Graphical abstract: Image 1 Highlights: Triboelectric effect is incorporated as a smart feature in the table which triggers an alarm upon intruder touches the desk. The triboelectric nanogenerator (TENG) works in the single electrode contact-separation mode as well as in sliding mode. Kapton film is the main triboelectric layer and the material on apparels, hand-skin acts as opposite triboelectric layer. The fabricated TENG coupled with Arduino board is placed to the table which triggers an alarm upon unauthorized access.